Navigating the Complex Landscape of Autism Spectrum Disorder: Challenges and Opportunities in Diagnosis, Treatment, and Supports - Sharma, Arun Kumar; Verma, Sant Kumar; Mehan, Sidharth (Current pharmaceutical design, 2025)
Autism Spectrum Disorder (ASD) is a complex neurodevelopmental condition characterized by persistent deficits in social communication and interaction, as well as restricted, repetitive patterns of behaviour, interests, or activities. Despite advancements in our understanding of ASD, identification, screening, diagnosing, and treating this condition present significant challenges. This review article comprehensively examines the current diagnostic and treatment landscape for ASD, addressing key issues and opportunities for improvement. The diagnostic criteria for ASD, as outlined in the Diagnostic and Statistical Manual of Mental Disorders-5 (DSM-5), provide a framework for identifying the condition. Still, the heterogeneity of presentation and the presence of comorbidities contribute to diagnostic complexity. Early intervention is crucial for improving outcomes in individuals with ASD; however, accessing timely and appropriate interventions can be challenging. A diverse range of interventions exists for individuals with ASD, including behavioural therapies, pharmacological treatments, gene expression, and alternative therapies. However, the efficacy and accessibility of these treatments vary, and navigating the treatment landscape can be daunting for caregivers and clinicians alike. Moreover, due to the persistence of healthcare disparities, , underserved populations face barriers to diagnosis and treatment. Transitioning to adulthood poses unique challenges for individuals with ASD, including finding employment and accessing support services. Additionally, ASD affects not only individuals diagnosed with the condition but also their families and caregivers. Addressing caregiver stress and burnout is essential for providing holistic care to individuals with ASD and their families. This review also identifies areas needing further research, such as personalized medicine and healthcare disparities, and discusses policy implications for enhancing ASD care and support. By highlighting research needs and policy considerations, this review aims to inform future efforts to improve ASD Screening, diagnosis, and treatment, ultimately striving to enhance outcomes for individuals with ASD and their families.